Preliminary study on the effects of treatment for breast cancer: immunological markers as they relate to quality of life and neuropsychological performance - Michael J. Boivin; Geoffrey P. Aaron; Nathan G. Felt; Lance Shamoun (BMC, 2020)
Abstract Background Immunological biomarkers were related to quality of life and neuropsychological performance in women recently diagnosed with breast cancer through the first six months of treatment. A comparison group of breast cancer survivors in remission were also evaluated. Method Twenty women newly diagnosed with breast cancer and 26 breast cancer survivors at least a year after treatment were evaluated four times over a course of six to 8 months. The assessments included quality-of-life, emotional and spiritual well-being, sleep quality, computerized neuropsychological performance, and cytokine immunology biomarkers using flow cytometry. The principal immunological markers examined were the CD4+, CD8+, and CD16+ counts. Results Although equivalent at enrollment, active treatment women reported higher anxiety, depression, poorer quality-of-life, and poorer processing speed and accuracy on memory, logical processes, and coding neuropsychological tasks. They also had significantly higher CD8+ and CD16+ cell count levels during treatment over the next six to eight months than comparison group women in remission. Women undergoing chemotherapy as well during treatment phase also had a significant decline in CD4+ counts. Higher percent CD8+ levels during treatment was associated with poorer quality of life and more depression, while higher CD4+ and CD8+ were associated with poorer neuropsychological memory and processing speed performance. Conclusion Significant increases in CD8+ is a sensitive biomarker of a broad range of poorer quality-of-life and neurocognitive functioning outcomes during breast cancer treatment, especially in women undergoing chemotherapy. Quality of life should be monitored in breast cancer patients and psychosocial support made available as a standard of care.